Mucinous Carcinoma of The Breast: Report of Two Cases (Journal of Surgical Sciences, 2019)
Mucinous carcinoma of the breast is one of 16 rare varieties of malignant lesions of epithelial origin Inbreast. They account for 1-6% of all breast cancer. Variations Inpresentation, cllnlcal course and prognosis has been observed in these patients. In this communication we report two cases of pure mucinous carcinoma of the breast .Both the cases were unusual, first one of them having early presentation with pulmonary and bone metastasis less commonly seen In this type of breast carcinoma and the second case had lymph node involvement that is seen in less than one fifth of the cases of mucinous carcinoma of breast. A brief review about mucinous carcinoma is supplemented with the report.Journal of Surgical Sciences (2013) Vol. 17 (1) : 45-49